2009
DOI: 10.4049/jimmunol.0803266
|View full text |Cite
|
Sign up to set email alerts
|

An Atopy-Associated Polymorphism in the Ectodomain of the IL-4Rα Chain (V50) Regulates the Persistence of STAT6 Phosphorylation

Abstract: Several commonly occurring polymorphisms in the IL-4Rα have been associated with atopy in humans; the Q576R and the S503P polymorphisms reside in the cytoplasmic domain, whereas the I50 to V50 polymorphism resides in the extracellular domain of the IL-4Rα. The effects of these polymorphisms on signaling remain controversial. To determine the effect of the polymorphisms on IL-4 signaling in human cells, we stably transfected the human monocytic cell line U937 with murine IL-4Rα cDNA bearing the I or V at positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 42 publications
(58 reference statements)
0
28
0
Order By: Relevance
“…41- 43 The p.Ile75Val polymorphism, named rs180510 on dbSNP, has been described as a gain-offunction mutation due to a sustained STAT6 phosphorylation. 44 This variant was associated with an increase in total serum IgE in atopic asthma, related to its active role in isotype class-switch recombination. 42 Thus, to identify a Most of the studies conducted in B-cell genes in different organ transplantation found an association with IL genes or tumor necrosis factor-α ( Table 1).…”
Section: Recipient-donor Genotype Discrepancy and Amrmentioning
confidence: 99%
“…41- 43 The p.Ile75Val polymorphism, named rs180510 on dbSNP, has been described as a gain-offunction mutation due to a sustained STAT6 phosphorylation. 44 This variant was associated with an increase in total serum IgE in atopic asthma, related to its active role in isotype class-switch recombination. 42 Thus, to identify a Most of the studies conducted in B-cell genes in different organ transplantation found an association with IL genes or tumor necrosis factor-α ( Table 1).…”
Section: Recipient-donor Genotype Discrepancy and Amrmentioning
confidence: 99%
“…We analyzed the impact of the Q576R, S503P, and I50V polymorphisms on signal transduction by the Type I receptor complex in vitro. While the R 576 and P 503 polymorphisms had no effect on STAT6 or IRS2 activation induced by IL-4 , we found that the V 50 polymorphism located in the extracellular domain of the IL-4R mediated a prolonged STAT6 signaling induced by IL-4 through the Type I receptor (Ford, et al, 2009). This was associated with a prolonged expression of the SOCS family member Cis.…”
Section: Single Nucleotide Polymorphisms Leading To Amino Acid Changementioning
confidence: 87%
“…The association of IL-4R I50V and RA may be explained by recent study of Ford et al, which found a direct effect of the V50 polymorphism in the IL-4Rα as it led to persistence of STAT6 activation in response to IL-4 and persistence activation of a STAT6-dependentgene [48].Since the V50 polymorphism is located in the extracellular domain of the IL-4Rαchain, the prolongation of STAT6 phosphorylationin V50-IL-4Rα was likely not due to modulation of these intracellular mechanisms [48]. The prolongation of STAT6 phosphorylationin V50-IL-4Rαwas dependent upon continued JAK activity [49].…”
Section: Discussionmentioning
confidence: 99%
“…The prolongation of STAT6 phosphorylationin V50-IL-4Rαwas dependent upon continued JAK activity [49]. Nevertheless, Ford et al, speculated that the V50 polymorphism may also impact glycosylation of the human IL-4Rαandthat the relative impact may be cell type specific [48]. This glycosylation could influence IL-4 binding parameters leading to alterations in persistence of IL-4 signaling and gene expression in human patients.…”
Section: Discussionmentioning
confidence: 99%